Pengelolaan Wakaf Uang sebagai Instrumen Pemberdayaan Ekonomi Keluarga - Muhammad Ash-Shiddiqy (STAI Pelabuhan Ratu, 2026)
Waqf is a religious institution in Islam that functionally has direct relevance to efforts to resolve social and humanitarian problems, such as poverty alleviation, human resource development and community economic empowerment. Unfortunately, according to the Indonesian Waqf Agency, waqf assets in Indonesia are not yet optimal due to the low level of public literacy. Waqf money has not been managed properly from the point of view of collection to distribution, even though the potential is high. The approach used in this study is a descriptive and qualitative analysis method, namely the data obtained is then compiled, making it easier to discuss existing problems. Analysis of the data that will be collected is by using qualitative and descriptive descriptive methods. The data that has been obtained is then arranged systematically so as to produce a clarity of the problem to be studied. This study aims to understand that cash waqf must be managed to support the economy in Indonesia. What can be done is to establish a Micro Waqf Bank as a forum to prepare borrowers to access formal financial institutions. So that with the existence of a Micro Waqf Bank (BWM) it can be more organized in terms of managing and developing waqf money, especially in helping social problems such as poverty and it is hoped that it can support the acceleration of the economy.